Three-Dimensional Organoid System Transplantation Technologies in Future Treatment of Central Nervous System Diseases - NaiLi Wei; ZiFang Quan; Hailiang Tang; JianHong Zhu (Hindawi Limited, 2017)
In recent years, scientists have made great achievements in understanding the development of human brain and elucidating critical elements of stepwise spatiotemporal control strategies in neural stem cell specification lineage, which facilitates successful induction of neural organoid in vitro including the cerebral cortex, cerebellar, neural tube, hippocampus cortex, pituitary, and optic cup. Besides, emerging researches on neural organogenesis promote the application of 3D organoid system transplantation in treating central nervous system (CNS) diseases. Present review will categorize current researches on organogenesis into three approaches: (a) stepwise, direct organization of region-specific or population-enriched neural organoid; (b) assemble and direct distinct organ-specific progenitor cells or stem cells to form specific morphogenesis organoid; and (c) assemble embryoid bodies for induction of multilayer organoid. However, the majority of these researches focus on elucidating cellular and molecular mechanisms involving in brain organogenesis or disease development and only a few of them conducted for treating diseases. In this work, we will compare three approaches and also analyze their possible indications for diseases in future treatment on the basis of their distinct characteristics.